Penggunaan Metode Dempster Shafer untuk Mendiagnosa Penyakit Varicella Zoster - Rahayu Utami; Novriyenni Novriyenni; Rusmin Saragih (Switch : Jurnal Sains dan Teknologi Informasi, 2024)
Varicella Zoster or known as chickenpox is an infectious disease caused by the Varicella Zoster virus (VSV). Chickenpox is a worldwide airbone disease. Transmission of Varicella zoster is through the air which spreads through coughing and sneezing and also through direct contact with skin lesions. This varicella disease is less of a concern for the public because of the assumption of the public that Varicella Zoster will heal on its own. Where there should be a consultation media and knowledge that can be used by the community in the prevention of varicella disease early on children. So that not every patient brought to the hospital was found to be a patient who had been infected for several days until it was severe to be treated and treated for Varicella Zoster disease. Varicella zoster disease consists of firepox (shingles) which is a follow-up infection of the virus that causes chickenpox. Chickenpox is a viral infection that causes itching on the skin and is characterized by a rash or red spots filled with fluid called elastic. The Dempster Shafer Method is the Dempster Shafer Method, which is a mathematical theory to prove based on belief function and plausibility. Belief indicates a measure of the strength of evidence in supporting a hypothesis, while plausibility indicates a state of trustworthiness. Based on the weight value given by experts on each Varivcella Zoster disease symptom data, from the results of the analysis carried out in the previous chapter, the results of the diagnosis of Varicella Zoster with the type of firepox disease (Herpes Zoster) with a density value of 98.08% were obtained. Keywords: Dempster Shafer, Diagnosis, Varicella Zoster